2018
DOI: 10.1038/s41598-018-28904-x
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Myopia: Contrast Polarity Matters

Abstract: In myopia the eye grows too long, generating poorly focused retinal images when people try to look at a distance. Myopia is tightly linked to the educational status and is on the rise worldwide. It is still not clear which kind of visual experience stimulates eye growth in children and students when they study. We propose a new and perhaps unexpected reason. Work in animal models has shown that selective activation of ON or OFF pathways has also selective effects on eye growth. This is likely to be true also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 36 publications
10
76
2
Order By: Relevance
“…Furthermore, the direction of changes in choroidal thickness matched previous findings with text of different contrast polarities, assumed to stimulate either ON or OFF pathways. 21 Our study has also shown that ON stimulation increases retinal DA release. Because DA has been implemented in the visual control of axial eye growth and myopia, the changes in DA may be involved in the changes in choroidal thickness.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Furthermore, the direction of changes in choroidal thickness matched previous findings with text of different contrast polarities, assumed to stimulate either ON or OFF pathways. 21 Our study has also shown that ON stimulation increases retinal DA release. Because DA has been implemented in the visual control of axial eye growth and myopia, the changes in DA may be involved in the changes in choroidal thickness.…”
Section: Discussionsupporting
confidence: 64%
“…Subfoveal choroidal area was imaged with SD-OCT (HRAþOCT Spectralis), as previously described. 21 Focus was adjusted for each subject depending on their spherical equivalent refractions. Because the choroid-sclera border was not well defined in some subjects, we used the EDI (enhanced depth imaging) mode of our OCT machine to improve visualization of the choroidal limits.…”
Section: Measurementsmentioning
confidence: 99%
See 3 more Smart Citations